2010
DOI: 10.1016/j.chom.2010.01.006
|View full text |Cite
|
Sign up to set email alerts
|

GM-CSF-Facilitated Dendritic Cell Recruitment and Survival Govern the Intestinal Mucosal Response to a Mouse Enteric Bacterial Pathogen

Abstract: Summary The attaching-and-effacing (A/E) lesion-causing enteric pathogen, Citrobacter rodentium, was used to probe the importance of GM-CSF in mucosal protection against enteric bacterial infection. C. rodentium infection increased GM-CSF production and CD11c+ dendritic cells (DC) in the colon of wild-type mice. After infection, mice lacking GM-CSF (GM-CSF-/-) had significantly fewer mucosal CD11c+ DC, greater bacterial burden, increased mucosal inflammation and systemic spread of infection, decreased antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
72
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 62 publications
6
72
1
2
Order By: Relevance
“…Murine inflammatory monocytes, the CD14 high human blood monocyte counterparts, are known to express CD62L and CCR2, allowing them to enter inflamed skin, but in line with Jackubzick et al (63) they might enter noninflamed peripheral tissues such as skin via hair follicles, as proposed by Nagao et al (65), and differentiate into macrophages, LCs, or remain as circulating monocytes according to the encountered environment. In line with this, sparse studies reported basal GM-CSF synthesis in human and murine skin or colonic mucosa, most predominantly by KCs and fibroblasts (66)(67)(68). Interestingly, Yasmin et al (40) have clearly shown that BMP-7 precedes TGF-b1 during embryonic life, between 8-10 and 9-11 wk estimated gestational age, respectively (69).…”
Section: Discussionmentioning
confidence: 62%
“…Murine inflammatory monocytes, the CD14 high human blood monocyte counterparts, are known to express CD62L and CCR2, allowing them to enter inflamed skin, but in line with Jackubzick et al (63) they might enter noninflamed peripheral tissues such as skin via hair follicles, as proposed by Nagao et al (65), and differentiate into macrophages, LCs, or remain as circulating monocytes according to the encountered environment. In line with this, sparse studies reported basal GM-CSF synthesis in human and murine skin or colonic mucosa, most predominantly by KCs and fibroblasts (66)(67)(68). Interestingly, Yasmin et al (40) have clearly shown that BMP-7 precedes TGF-b1 during embryonic life, between 8-10 and 9-11 wk estimated gestational age, respectively (69).…”
Section: Discussionmentioning
confidence: 62%
“…GM-CSF is produced at low levels in various tissues, including the intestine in the steady state, and is further induced during inflammation and infection. 20,21 Indeed, IEC-SN obtained from PTK6 cell monolayers contained low concentrations of GM-CSF (56 Ϯ 7.5 pg/ mL, n ϭ 3). Pretreatment of IEC-SN with neutralizing antibody against GM-CSF largely abrogated down-regulation of BST2 ( Figure 5A) and the enhanced inflammatory cytokine production in FL-DCs exposed to IEC-SN ( Figure 5B).…”
Section: Generation Of Cd11b ؉ Mhcii High Cdc-like Cells From Ccr9 ؊ mentioning
confidence: 99%
“…The host defense against C. rodentium comprises sequential contributions from different immune cell populations, including a variety of type 3 ILC (ILC3) subsets, dendritic cells, and adaptive immune cells, including T and B lymphocytes (15)(16)(17)(18)(19)(20). Several studies have suggested an important role for Th17 cells during the course of C. rodentium infection (21)(22)(23).…”
mentioning
confidence: 99%